UJI ANTIBAKTERI EKSTRAK BATANG KECOMBRANG (Nicolaia speciosa Horan) TERHADAP Staphylococcus aureus DAN Escherichia coli - Ancela Rabekka Lingga; Usman Pato; Evy Rossi (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2016)
The aims of the research were to learn capability antibacterial of kecombrang stem extract againts the growth Staphylococus aureus and Escherichia coli and to determine the Minimum Inhibitory Concentration (MIC) score. This research conducted an experimently by the antibacterial activity of  kecombrang stem extracts by using polar, nonpolar and semipolar solvents against S. aureus and E. coli. The antibacterial activity was tested by using  paper disk  diffusion method and Minimum Inhibitory Concentration (MIC) score by using dilution. The data obtained were tabulated and analysed descriptively. The antibacterial test show that ethyl acetate extract formed clear zone ranged between 1-3,5 mm in diameters, wich was higher than water extract (0,73-3,16 mm) and hexane extract (0,8-1,8 mm) kecombrang stem. Scores MIC show that ethyl acetate extract of kecombrang stem that inhibited the growth of E. coli dan S. aureus at concentration of 20 and 40% and extract water of  kecombrang stem inhibited the growth  of E. coli at concentration 80% and S. aureus at concentration of 40%. Meanwhile hexane extract of kecombrang stem inhibited the growth of E. coli and S. aureus at concentration 100%. Keyword: Antibacterial, Kecombrang stem, E coli, S. aureus,